The development system and circuit design of buck boost converter for PV solar system - Nurshuhadah, Zaharudin (2018)
The Buck Boost Converter for PV solar system is a product used to regulate the PV solar system voltage output to be constant. The PV solar system will be connected to the buck boost converter. In this project, the closed loop system of the buck boost can be produced by controlling the switching through pulse width modulator (PWM) duty cycle. The Arduino microcontroller is suitable for controlling the PWM duty cycle. The developed system using both simulation and prototype and the desired output voltage was gain from both method. A buck boost converter for PV solar system was successfully developed and designed.